Investigation on Phytochemical and Antioxidant Activity of the Plant Murraya koenigii Linn (Curry leaf) in Rajshahi, Bangladesh - Dahlia, Ismat Ara; Islam, Md. Badrul; Zaman, Shahed; Islam, Md. Asadul; Jalil, Md. Abdul; Ahmed, Nazim Uddin; Rahim, Md. Abdur; Mondol, Md. Mahmudul Hassan; Ali, Ahsan Muzahid; Sarkar, Murshed Hasan (Journal of Antioxidant Activity, 2017)
The use of herbal medicine is becoming popular day by day due to toxicity and side effects of allopathic medicines. Considering the medicinal importance of the plant Murraya koenigii Linn (Curry leaf), the antioxidant activity (AC), total phenolic content (TPC), total flavonoid content (TFC), of different fractions of methanolic extract (DIA-ion resin adsorbed fraction, chloroform, Ethyl acetate and petroleum ether) of M. koenigii were investigated. Among the fractions, DIA-ion resin-adsorbed fraction showed the highest total antioxidant activity with absorbance 2.320±06 and petroleum ether fraction showed the lowest total antioxidant activity with absorbance 1.944 at 100 mg/ml concentration. The TPC were found range between 13.285 to 17.52 mg GAE/g while the highest amount of TFC recorded among the extracts was 16.65 mg CatE/g. DPPH free radical scavenging activity of different extracts of leaves was also measured where DIA-ion resin-adsorbed fraction had the highest free radical scavenging activity with IC50 value 15.53 µg/ml. In the present study phenolic compound were found to be the predominant components in the leaves of M. koenigii indicating that they are potent antioxidant.
Keywords: Murraya koenigii Linn; Antioxidant; Crude extract; free radical; scavenging